2018
DOI: 10.22571/2526-433868
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization and pharmacological action of Brazilian red propolis

Abstract: Among natural products, Brazilian propolis stands out for being considered a source for the discovery of new bioactive compounds. In the last decade, a new Brazilian propolis has been described, known as red propolis due to its reddish pigment. Since then, numerous studies revealing its major components and pharmacological activity have been carried out. Thus, this research had the aim of performing an integrative review of literature on the biological activity of Brazilian red propolis. Scientific studies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Compared to green or brown propolis, the red Brazilian propolis is rich in polyphenols, more than 30 different phenolic compounds have been identified so far [ 9 , 46 , 53 ] and more than 300 components from different chemical classes have been identified [ 55 ]. Unlike other types of propolis, red propolis has a specific chemical composition presenting some compounds never before reported in other propolis types, such as vestitol and neovestitol, biochamine A, as well as liquiritigenin, formononetine, and medicarpine [ 2 ].…”
Section: Propolis Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to green or brown propolis, the red Brazilian propolis is rich in polyphenols, more than 30 different phenolic compounds have been identified so far [ 9 , 46 , 53 ] and more than 300 components from different chemical classes have been identified [ 55 ]. Unlike other types of propolis, red propolis has a specific chemical composition presenting some compounds never before reported in other propolis types, such as vestitol and neovestitol, biochamine A, as well as liquiritigenin, formononetine, and medicarpine [ 2 ].…”
Section: Propolis Chemical Compositionmentioning
confidence: 99%
“…One of the characteristics of this lipophilic material is that it is hard and brittle when cold, and soft, pliable, and very sticky when warm; for this reason, sometimes it is named “bee glue” [ 2 ]. It has an aromatic smell, and different colors, depending on its source, period of harvesting, and time of storage in the hive.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis and geopropolis has aroused a growing interest among researchers and many studies have been conducted on its chemical composition and pharmacological activities. Thus, research has confirmed several biological activities such as antimicrobial, anti-inflammatory, antioxidant, hepatoprotective, antitumor and healing activities, and the effectiveness in the treatment of burns, wounds and ulcers, among others, have been reported in scientific article (Afrouzan et al, 2018;Cardinault et al, 2012;Castro & Salgueiro, 2016;Pontes et al, 2018;Kunrath et al, 2017).…”
Section: Introductionmentioning
confidence: 78%
“…This result demonstrates the variety in propolis chemical composition, although some authors have found these compounds in samples of red propolis. It is known that propolis chemical composition varies according to original geographic region, and propolis phytochemical profile can vary due to several factors such as local flora, season, and extraction methods, resulting in different extracts ( Alencar et al, 2007 ; Cavalcanti de Pontes et al, 2018 ; do Nascimento et al, 2019 ). da Silva Frozza et al (2017) identified some compounds of biological interest, such as isoflavones formononetin, and biochanin A besides isoliquiritigenin in samples of red propolis from Alagoas.…”
Section: Resultsmentioning
confidence: 99%
“…such as local flora, season, and extraction methods, resulting in different extracts (Alencar et al, 2007;Cavalcanti de Pontes et al, 2018;do Nascimento et al, 2019). da Silva Frozza et al (2017) identified some compounds of biological interest, such as isoflavones formononetin, and biochanin A besides isoliquiritigenin in samples of red propolis from Alagoas.…”
Section: Independent Variables Levelsmentioning
confidence: 99%